E-commerce Last-mile Supply Network Configuration and Logistics Capability - Stanley Frederick W. T. Lim; Jagjit Singh Srai (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
The exact mechanism as to how last-mile supply network (LMSN) configuration influences performance has been relatively undeveloped, and with mixed results in the extant literature. This paper argues the difficulty in arriving to a convergent understanding because of a missing link that connects the relationship between configuration and performance. Specifically, it is posited that the missing link lies in the mediating role of logistics capability (comprising demand-management interface; supply- management interface; information management; and co-ordination) on the relationship between LMSN configuration and performance. Using the configurational approach, six configuration dimensions are identified: consumer portfolio; product portfolio; network structure; network flow; relationship and governance; and service architecture. By incorporating greater precision and additional theoretical considerations, this paper presents a conceptual framework through a set of propositions that provides greater depth of insight regarding the relationship between the influencing factors on LMSN configuration with logistics capability and performance.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Last-Mile Supply Network; Configuration; Logistics Capability; E-Commerce